The moral appropriateness of shame - Ally, M. (Koers, 2005)
In this article I explore the much neglected moral emotion of shame and consider the senses in which it may be regarded as morally appropriate. I argue that there is a connection between coming to terms with shame for those who feel ashamed, and judgments concerning its moral appropriateness. The elucidation of normative connections between shame, self-respect and autonomy implies the need to accept certain aspects of shame as regrettable yet, sometimes, as valuable.